Green HSR Reliable Communication With LTE-R Using MIMO-DPD - Anurag Vijay Agrawal; Meenakshi Rawat (IEEE Access, 2021)
Reliable and efficient High-speed Railways (HSR) is the key component to the concept of Green Smart Cities to combat the prevailing traffic congestion on roads and increasing greenhouse gases in the atmosphere. It is also a fast, safe, and economical transport medium. Long Term Evolution – Railways (LTE-R), though in the developing stage, is a new wireless communications standard for providing intelligent broadband communication services to passengers and train operators. Reliable HSR communication requires more base stations (BSs). The radio frequency power amplifier (RFPA), an integral part of the BS, dominates the overall energy consumption and is inherently nonlinear. Digital Predistortion (DPD), the ultimate Green communication technique, is used to linearize RFPAs and provide less power waste. Multiple-input-multiple-output (MIMO) schemes have been used to achieve enhanced data throughputs and superior transmission reliability. This paper analyzes the effect of DPD arrangement corresponding to these schemes for reliable HSR communication in infrastructure-to-train and inside-station scenarios. The authors consider downlink transmission for the LTE-R specifications at different train speeds. Furthermore, the paper proposes an analytical framework to evaluate the performance of the complete HSR MIMO communications system. This analytical framework characterizes the antenna effects on the Block Error Rate (BLER) and throughput by adopting various transmission modes, viz. SISO, MISO, SIMO and MIMO. Numerical analyses and simulations for the proposed system illustrate better reliability and high throughput performances with higher-order MIMO configurations. Moreover, significant energy savings can be realized by universally deploying DPD across the HSR network in Smart Cities.